2017
DOI: 10.1073/pnas.1706541114
|View full text |Cite
|
Sign up to set email alerts
|

Buying time promotes happiness

Abstract: Around the world, increases in wealth have produced an unintended consequence: a rising sense of time scarcity. We provide evidence that using money to buy time can provide a buffer against this time famine, thereby promoting happiness. Using large, diverse samples from the United States, Canada, Denmark, and The Netherlands (n = 6,271), we show that individuals who spend money on time-saving services report greater life satisfaction. A field experiment provides causal evidence that working adults report great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
126
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(136 citation statements)
references
References 29 publications
5
126
0
5
Order By: Relevance
“…It has been argued that time scarcity prevents increases of consumption from being experienced in a meaningful way and therefore from leading to an increase in life satisfaction [20]. Empirically, it has been shown that spending money on time-saving but energy-intensive services can protect working adults from such adversary effects [21]. Moreover, it has been shown that the experience of time affluence is positively related to subjective well-being, partly because time affluence allows for the better satisfaction of psychological needs, such as autonomy, competence, and relatedness [22].…”
Section: Introductionmentioning
confidence: 99%
“…It has been argued that time scarcity prevents increases of consumption from being experienced in a meaningful way and therefore from leading to an increase in life satisfaction [20]. Empirically, it has been shown that spending money on time-saving but energy-intensive services can protect working adults from such adversary effects [21]. Moreover, it has been shown that the experience of time affluence is positively related to subjective well-being, partly because time affluence allows for the better satisfaction of psychological needs, such as autonomy, competence, and relatedness [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, a limitation of these results is that we asked participants about their perception of these jobs after they had already made their decision about which jobs they would have preferred; thus, these results were biased by the decisions that individuals made immediately prior to providing their responses. Furthermore, although we modelled these questions after previously published research (Whillans et al, 2017), we only used single item measures to assess our key constructs of interest. To overcome these limitations, we conducted a more formal test of whether monetization shifted perceptions of the organization.…”
Section: Study 1a-study 3 Discussionmentioning
confidence: 99%
“…After making their decision, participants completed a 9-item measure assessing why made this decision. We adapted this measure from previous research assessing differences in purchase characteristics (Whillans et al, 2017). Specifically, we asked participants to report the extent to which they selected the job because the organization was more fun, higher in status, had more opportunity for advancement, cared more about employees, had a better salary, better benefits, better total compensation (salary/benefits), or because they thought the organization had better work-life balance.…”
Section: Study 1amentioning
confidence: 99%
“…a variable that is caused both by resources and by relationship quality (see e.g. Whillans et al (2017)).…”
Section: Methodsmentioning
confidence: 99%